Experimental study on photovoltaic panel integrated with Polyethylene Glycol 1500 phase change material. (15th November 2022) - Bhakre, Someshwar S.; Sawarkar, Pravin D.; Kalamkar, Vilas R.
Abstract: The heat generated during solar photovoltaic (PV) operation increases the PV cells temperature and reduces electric power generation. Several cooling strategies have been used to remove the heat generated during the process. One of them is the addition of a layer of phase change materials on the backside of PV panel, which can control PV temperature rise and result in increased electrical conversion efficiency and power output. In this paper, the use of novel Polyethylene Glycol 1500 (PEG 1500) as phase change material (PCM) has been explored. Also, the effect of metal matrix insertion into phase change material integrated with PV has been presented. A comparative study has been done for PV/PCM with and without metal matrices. The Polyethylene Glycol 1500 has a melting temperature in the range of 50 °C–56 °C. PV panel's thermal and electrical performance in outdoor conditions is experimentally investigated. The results indicate that use of PEG 1500 as PCM decreases PV panel temperature by 10.59 % and 14.08 % and enhances electrical efficiency by 5.84 % and 8.87 % for PV/PCM and PV/PCM metal matrix systems, respectively. However, the power output of 40 W panel increases by 2 W and 3.5 W for PV/PCM and PV/PCM metal matrix systems, respectively, when the solar intensity is at its peak. Highlights: Experimentally investigated the performance of PV/PCM (PEG1500) system. PV/PCM metal matrix performed better than PV/PCM system. Applied cooling system reduces panel temperature by 10.59 %–14.08 %. Applied cooling system improves electrical efficiency by 5.84 %–8.87 %. The water circulation network is suggested for PV/PCM system optimization.